European Baseline Series, Polish Baseline Series, Polish Standard… Why compositions of patch test series undergo revisions and how does it influence clinical practice? - Radosław Śpiewak; Grzegorz Ostrowski; Ewelina Szendzielorz; Jadwiga Kalicińska (Alergologia Polska)
Experts agree that patch test is nowadays the only validated method for the detection of contact allergy to haptens. Facing more than 5200 known haptens, starting with sensitizers most frequent in a given population seems most reasonable. Baseline series for patch testing are the answer to practitioners’ needs with this regard. The composition of baseline series greatly influences the diagnostic effectiveness of patch tests. “Polish Set of Contact Allergens” (1970) was the first baseline series in Poland, while “Standard European Series” (1974) was the starting point for modern European Baseline Series. Due to constant changes in exposures, baseline series must undergo regular revisions. The present paper discusses methodology, criteria, and history of such revisions. Changes in baseline series result from: 1) progress in medical knowledge, e.g., epidemiological trends; 2) technological progress, e.g. improved vehicles; 3) technical problems, including difficulty in obtaining high-quality raw materials, and 4) legal barriers (overregulation that may deter producers from introducing new haptens and keeping those already on the market). Influence of these factors on the present Polish Standard I (PS I) series are discussed and new haptens in PS I presented in detail: benzisothiazolinone, decyl glucoside, carvone, sodium metabisulfite, toluene-2,5-diamine sulfate, sorbitan sesquioleate and disperse blue mix 106/124. The authors conclude that changes in baseline series are unavoidable, because of changes in the external world and technological progress. They also warn that the present tendency to overregulate diagnostic haptens in Europe could lead to a situation in which doctors would not anymore be able to effectively contain new waves of sensitizations similar to epidemics of contact allergy in the past.